The negative existential cycle in Chadic - Butters, Marielle (My University, 2022)
Chadic languages, like languages of West and Central Africa more generally, are known to make use of typologically rare negation strategies. Not only do many Chadic languages exhibit bi-partite negation, there is also a tendency for the second of these two verbal negators to occur after the verb, in contrast to a cross-linguistic preference for pre-verbal negation. This particular study examines the extent to which Croft’s (1991) Negative Existential Cycle (NEC) may be demonstrated across Chadic languages. Furthermore, the study explores the use of the NEC as an explanatory framework in determining sources and pathways of verbal negation in Chadic languages. An important implication of this study is that identification of the B~C stage of the NEC elucidates the relationship between verbal negation and negative existential predication, as well as the relationship between these domains and other domains of the grammar such as aspect.
Keywords: existential predication; cyclical change; Chadic